Sistem Informasi Geografis Pemetaan Lokasi Mall di Baturaja Berbasis Web - Desta, M. Dion Regan; Alfino, Edwin; Hasbi, Jefri Akbar Al; Pujianto, Pujianto (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to develop a Geographic Information System (GIS) that presents accurate and easily accessible information on the locations of malls and shopping centres in the Baturaja area. As the capital of Ogan Komering Ulu (OKU) Regency, Baturaja has experienced rapid development in the trade sector, but the distribution of malls and shopping centres has not been systematically documented, making it difficult for the public to find the locations they need. This study uses the waterfall model software development method, which includes the stages of requirements analysis, system design, implementation, testing, and maintenance. Mall location data was obtained through secondary data collection and field observations, then mapped using the Google My Maps platform. System testing was carried out using the blackbox testing method to ensure that all functions ran according to user requirements. The results of the study show that the developed GIS system is capable of displaying mall locations visually in the form of digital maps, providing attribute information for each mall, and facilitating users in searching for locations. Thus, the mall mapping GIS in Baturaja can be an effective information medium to support the needs of the community and visitors in accessing shopping centres quickly and accurately